Narcisismi: l'opera di Walter Siti attraverso i paradigmi di Byung-Chul Han. - Matteo Moca (Between, 2018)
With the publication of The culture of Narcissism in 1979, Christopher Lasch had spotted the chararchteristics of a solipsistic attitude which, with the beginning of contemporaneity, would be subjected to a further worsening. Philosopher Byung-Chul Han's reflections seem to carry on Lasch's researches. Han shapes a speech based on contemporary society and its mechanisms in relation to the changes taken by digital screens. The greatest risk, according to Han, is the one which hits the basis of the social living of the man. A man who today is busier and busier in satisfying himself and outdoing the neighbor. Walter Siti's works show the diseases of of this contemporaneity which somehow refer to digital revolution which touches, first of all, TV world and then the one of new devices. In this way, a fundamental discussion can start: the one about reality which is anesthetized and “weakened”. Starting from Lash's reflections and going through Byung-Chul Han's essays, Walter Siti's work can be examined properly. We can try to create a story about contemporary charter of the screens, of narcissism and of narration of reality.